2018
DOI: 10.1002/adsc.201701201
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sulfonated 5‐Aminopyrazoles by I2/Benzoyl Peroxide‐Mediated Tandem Reaction

Abstract: The tandem reaction of 3-morpholinoacrylonitrile with sulfonyl hydrazides mediated by I 2 / benzoyl peroxide (BPO) is reported, which offers an efficient approach for the synthesis of sulfonated 5-aminopyrazoles. It can bear a large scope of the substrates, and be used for the synthesis of aromatic, heteroaromatic and aliphatic sulfonated 5-aminopyrazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Yan and co‐workers reported the I 2 /BPO (benzoyl peroxide)‐mediated tandem reaction of 3‐morpholinoacrylonitrile with sulfonyl hydrazides (Eq. 8‐1).…”
Section: Sulfonyl Radiacls‐mediated Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan and co‐workers reported the I 2 /BPO (benzoyl peroxide)‐mediated tandem reaction of 3‐morpholinoacrylonitrile with sulfonyl hydrazides (Eq. 8‐1).…”
Section: Sulfonyl Radiacls‐mediated Reactionsmentioning
confidence: 99%
“…In our opinion, a summary classified by crucial intermediates will do much to help the application of diverse methodologies. As shown in Scheme , our review is based on ten categories: (1) sulfonyl radiacls; (2) thiosulfonates; (3) ArS . radicals; (4) sulfur‐centered anions; (5/6) metallo‐organic compounds with or without sulfonyl moiety; (7/8) electrophilic RSX or RS‐DBU intermediates; (9) nucleophilic hydrazines; (10) sulfonyl hydrazides as diazene or sulfinic acid surrogate.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, the tandem reaction of 3-morpholinoacrylonitrile with sulfonyl hydrazides mediated by I 2 /benzoyl peroxide (BPO) was described by Yan group. [114] Control experiments showed that free radical was involved in the reaction mechanism and 1tosyl-1H-pyrazol-5-amine was not the intermediate in this reaction. Sulfonyl radical which was formed from sulfonyl hydrazine by the removal of nitrogen in the presence of benzoyl peroxide and iodine was also proposed in the reaction mechanism (Scheme 100).…”
Section: Sulfonylation/noncyclization With Alkenesmentioning
confidence: 97%
“…The reaction mechanism includes formation of the sulfonyl radical under oxidative conditions, its subsequent addition to the activated double bond, interception of the formed C-centered radical with iodine, nucleophilic substitution of iodine by sulfonyl hydrazide 434, elimination of the morpholine moiety, and intramolecular cyclization. [240] Three-component condensation of amidines 436, ynals 437, and sodium sulfinates 438 led to 4sulfonylmethyl imidazoles 439 or 5-sulfonylmethyl imidazoles 440 depending on the reaction conditions. Performance of the reaction in EtOH in the presence of AcOH delivered 4-sulfonyl derivatives, while conduct-ing the process in MeCN and addition of TBHP as the oxidant resulted in 5-sulfonyl derivatives (Scheme 193).…”
Section: Construction Of Five-membered Heterocyclesmentioning
confidence: 99%